THE HIGHER ORDER THINKING SKILL OF PRE-SERVICE TEACHER ACCORDING TO VAN HIELE’S THEORY OF THOUGHT IN ANALYSIS LEVEL - Pakaya, Widi Candika; Sutadji, Eddy; Mashfufah, Aynin (Universitas Muhammadiyah Ponorogo, 2024)
The purpose of this study was to characterize teacher candidate students' higher-order thinking skills (HOTS) using the Van Hiele analysis level. The qualitative descriptive method was employed in this study. The Van Hiele Geometry Test and the HOTS test served as the research instruments. Data were gathered via tests and interviews. Next, two participants who, in accordance with Van Hiele's theory, had attained the analytical level among third-semester primary school teacher education students served as the research subjects. According to Van Hiele's theory, the research's findings indicated that the students who attained the analysis level were unable to meet HOTS indicators including analysis, evaluating, and creativity indicators. Since the students did not state proper reasons to support the conclusion, which it was used during the process of conclusion.